Rancang Bangun Smart Plug Untuk Sistem Monitoring Dan Proteksi Hubungsingkat Listrik - Arto, Budi; Winarno, Basuki; Hidayatullah, Nur Asyik (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2019)
The development of technology is expected to help humans in quality of life. The industrial world is making preparations for industrial revolution 4.0 which is designed to integrate the online world with production lines in industrial processes. All production processes in the 4.0 era and running with the internet as support. The internet has become one of the human's main needs. At present, the development of the internet has not yet developed with the development of protection and control systems in the electricity sector. A breakthrough is needed to create the necessary protection systems and also control the load. A Smart Plug is a breakthrough that can accommodate this. Relays available on Smart Plugs can be used as protection and control devices on household electrical appliances. To read current and load, the current sensor (ZHT 03) and voltage sensor (ZMPT101B) are used. All sensor and relay data is performed by Arduino Nano. Whereas NodeMCU 12-E is used to connect the Smart Plug with the web and database. Smart Plug test results with the web site show that Smart Plug can work well on protection and control systems. This is evidenced by the interrupted current flowing at the load, the load compilation current is more than the value of the current that has been determined as the set point. While the control system can also work optimally. Relays can be received according to orders given from the website.